Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
Sure! Let's go through each of the questions one by one.
### Question 15
#### (a) Solve [tex]\(\tan^2 \theta - 3 = 0\)[/tex]
1. Rearrange the equation: [tex]\(\tan^2 \theta = 3\)[/tex].
2. Take the square root of both sides: [tex]\(\tan \theta = \sqrt{3}\)[/tex].
3. Using the known angle values, [tex]\(\tan \theta = \sqrt{3}\)[/tex] corresponds to [tex]\(\theta = 60^\circ\)[/tex].
So, [tex]\(\theta = 60^\circ\)[/tex].
#### (d) Solve [tex]\((2 \sin \theta - 1)(\sin \theta - 2) = 0\)[/tex]
1. Set each factor to zero:
- [tex]\(2 \sin \theta - 1 = 0 \implies \sin \theta = \frac{1}{2}\)[/tex]
- [tex]\(\sin \theta - 2 = 0 \implies \sin \theta = 2\)[/tex]
2. [tex]\(\sin \theta = \frac{1}{2}\)[/tex] corresponds to [tex]\(\theta = 30^\circ\)[/tex].
- Note: Since [tex]\(\sin \theta\)[/tex] cannot be greater than 1, [tex]\(\sin \theta = 2\)[/tex] is not a valid solution.
So, [tex]\(\theta = 30^\circ\)[/tex].
#### (c) Solve [tex]\(2 \cos^2 \theta - 1 = 0\)[/tex]
1. Rearrange the equation: [tex]\(2 \cos^2 \theta = 1 \implies \cos^2 \theta = \frac{1}{2}\)[/tex].
2. Take the square root of both sides: [tex]\(\cos \theta = \frac{\sqrt{2}}{2}\)[/tex].
[tex]\(\cos \theta = \frac{\sqrt{2}}{2}\)[/tex] corresponds to [tex]\(\theta = 45^\circ\)[/tex].
So, [tex]\(\theta = 45^\circ\)[/tex].
#### (e) Solve [tex]\(2 \cos^2 \theta + \cos \theta - 1 = 0\)[/tex]
This is a quadratic equation in [tex]\(\cos \theta\)[/tex]. Let [tex]\(x = \cos \theta\)[/tex]:
1. The quadratic equation becomes: [tex]\(2x^2 + x - 1 = 0\)[/tex].
2. Factoring the quadratic equation, we get: [tex]\((2x - 1)(x + 1) = 0\)[/tex].
3. Solve for [tex]\(x\)[/tex]:
- [tex]\(2x - 1 = 0 \implies x = \frac{1}{2}\)[/tex]
- [tex]\(x + 1 = 0 \implies x = -1\)[/tex]
For [tex]\(0^\circ \leq \theta \leq 90^\circ\)[/tex]:
- [tex]\(\cos \theta = \frac{1}{2}\)[/tex] corresponds to [tex]\(\theta = 60^\circ\)[/tex].
- [tex]\(\cos \theta = -1\)[/tex] is not valid as [tex]\(\theta\)[/tex] must be within [tex]\(0^\circ\)[/tex] to [tex]\(90^\circ\)[/tex].
So, [tex]\(\theta = 60^\circ\)[/tex].
### Question 16
Given [tex]\(2 \sin^2 \theta - 1 = 0\)[/tex]:
1. Rearrange the equation: [tex]\(\sin^2 \theta = \frac{1}{2}\)[/tex].
2. Take the square root: [tex]\(\sin \theta = \frac{\sqrt{2}}{2}\)[/tex].
When [tex]\(\sin \theta = \frac{\sqrt{2}}{2}\)[/tex], [tex]\(\theta = 45^\circ\)[/tex].
#### (a) Find [tex]\(\cos \theta + \cos 2\theta\)[/tex]
- [tex]\(\cos 45^\circ = \frac{\sqrt{2}}{2}\)[/tex].
- [tex]\(\cos 2\theta = \cos 90^\circ = 0\)[/tex].
So, [tex]\(\cos \theta + \cos 2\theta = \frac{\sqrt{2}}{2} + 0 = \frac{\sqrt{2}}{2}\)[/tex].
#### (b) Find [tex]\(\sin \theta \cdot \sin 2\theta\)[/tex]
- [tex]\(\sin 45^\circ = \frac{\sqrt{2}}{2}\)[/tex].
- [tex]\(\sin 2\theta = \sin 90^\circ = 1\)[/tex].
So, [tex]\(\sin \theta \cdot \sin 2\theta = \frac{\sqrt{2}}{2} \cdot 1 = \frac{\sqrt{2}}{2}\)[/tex].
### Question 17
Given [tex]\(\theta\)[/tex] is an acute angle and [tex]\(\cos \theta = \sin \theta\)[/tex]:
1. [tex]\(\cos \theta = \sin \theta \implies \theta = 45^\circ\)[/tex].
#### (a) Find [tex]\(2 \tan^2 \theta + \cos^2 \theta - 1\)[/tex]
- [tex]\(\theta = 45^\circ\)[/tex].
- [tex]\(\tan 45^\circ = 1\)[/tex], so [tex]\(\tan^2 45^\circ = 1\)[/tex].
- [tex]\(\cos 45^\circ = \sin 45^\circ = \frac{\sqrt{2}}{2}\)[/tex], so [tex]\(\cos^2 45^\circ = \frac{1}{2}\)[/tex].
Thus,
[tex]\[ 2 \tan^2 \theta + \cos^2 \theta - 1 = 2 \cdot 1 + \frac{1}{2} - 1 = 2 + \frac{1}{2} - 1 = 1 + \frac{1}{2} = \frac{3}{2}. \][/tex]
#### (b) Find [tex]\(2 \cos^2 \theta - 1\)[/tex]
- [tex]\(\cos 45^\circ = \frac{\sqrt{2}}{2}\)[/tex], so [tex]\(\cos^2 45^\circ = \frac{1}{2}\)[/tex].
Thus,
[tex]\[ 2 \cos^2 \theta - 1 = 2 \cdot \frac{1}{2} - 1 = 1 - 1 = 0. \][/tex]
With these detailed steps, we have solved all the problems.
### Question 15
#### (a) Solve [tex]\(\tan^2 \theta - 3 = 0\)[/tex]
1. Rearrange the equation: [tex]\(\tan^2 \theta = 3\)[/tex].
2. Take the square root of both sides: [tex]\(\tan \theta = \sqrt{3}\)[/tex].
3. Using the known angle values, [tex]\(\tan \theta = \sqrt{3}\)[/tex] corresponds to [tex]\(\theta = 60^\circ\)[/tex].
So, [tex]\(\theta = 60^\circ\)[/tex].
#### (d) Solve [tex]\((2 \sin \theta - 1)(\sin \theta - 2) = 0\)[/tex]
1. Set each factor to zero:
- [tex]\(2 \sin \theta - 1 = 0 \implies \sin \theta = \frac{1}{2}\)[/tex]
- [tex]\(\sin \theta - 2 = 0 \implies \sin \theta = 2\)[/tex]
2. [tex]\(\sin \theta = \frac{1}{2}\)[/tex] corresponds to [tex]\(\theta = 30^\circ\)[/tex].
- Note: Since [tex]\(\sin \theta\)[/tex] cannot be greater than 1, [tex]\(\sin \theta = 2\)[/tex] is not a valid solution.
So, [tex]\(\theta = 30^\circ\)[/tex].
#### (c) Solve [tex]\(2 \cos^2 \theta - 1 = 0\)[/tex]
1. Rearrange the equation: [tex]\(2 \cos^2 \theta = 1 \implies \cos^2 \theta = \frac{1}{2}\)[/tex].
2. Take the square root of both sides: [tex]\(\cos \theta = \frac{\sqrt{2}}{2}\)[/tex].
[tex]\(\cos \theta = \frac{\sqrt{2}}{2}\)[/tex] corresponds to [tex]\(\theta = 45^\circ\)[/tex].
So, [tex]\(\theta = 45^\circ\)[/tex].
#### (e) Solve [tex]\(2 \cos^2 \theta + \cos \theta - 1 = 0\)[/tex]
This is a quadratic equation in [tex]\(\cos \theta\)[/tex]. Let [tex]\(x = \cos \theta\)[/tex]:
1. The quadratic equation becomes: [tex]\(2x^2 + x - 1 = 0\)[/tex].
2. Factoring the quadratic equation, we get: [tex]\((2x - 1)(x + 1) = 0\)[/tex].
3. Solve for [tex]\(x\)[/tex]:
- [tex]\(2x - 1 = 0 \implies x = \frac{1}{2}\)[/tex]
- [tex]\(x + 1 = 0 \implies x = -1\)[/tex]
For [tex]\(0^\circ \leq \theta \leq 90^\circ\)[/tex]:
- [tex]\(\cos \theta = \frac{1}{2}\)[/tex] corresponds to [tex]\(\theta = 60^\circ\)[/tex].
- [tex]\(\cos \theta = -1\)[/tex] is not valid as [tex]\(\theta\)[/tex] must be within [tex]\(0^\circ\)[/tex] to [tex]\(90^\circ\)[/tex].
So, [tex]\(\theta = 60^\circ\)[/tex].
### Question 16
Given [tex]\(2 \sin^2 \theta - 1 = 0\)[/tex]:
1. Rearrange the equation: [tex]\(\sin^2 \theta = \frac{1}{2}\)[/tex].
2. Take the square root: [tex]\(\sin \theta = \frac{\sqrt{2}}{2}\)[/tex].
When [tex]\(\sin \theta = \frac{\sqrt{2}}{2}\)[/tex], [tex]\(\theta = 45^\circ\)[/tex].
#### (a) Find [tex]\(\cos \theta + \cos 2\theta\)[/tex]
- [tex]\(\cos 45^\circ = \frac{\sqrt{2}}{2}\)[/tex].
- [tex]\(\cos 2\theta = \cos 90^\circ = 0\)[/tex].
So, [tex]\(\cos \theta + \cos 2\theta = \frac{\sqrt{2}}{2} + 0 = \frac{\sqrt{2}}{2}\)[/tex].
#### (b) Find [tex]\(\sin \theta \cdot \sin 2\theta\)[/tex]
- [tex]\(\sin 45^\circ = \frac{\sqrt{2}}{2}\)[/tex].
- [tex]\(\sin 2\theta = \sin 90^\circ = 1\)[/tex].
So, [tex]\(\sin \theta \cdot \sin 2\theta = \frac{\sqrt{2}}{2} \cdot 1 = \frac{\sqrt{2}}{2}\)[/tex].
### Question 17
Given [tex]\(\theta\)[/tex] is an acute angle and [tex]\(\cos \theta = \sin \theta\)[/tex]:
1. [tex]\(\cos \theta = \sin \theta \implies \theta = 45^\circ\)[/tex].
#### (a) Find [tex]\(2 \tan^2 \theta + \cos^2 \theta - 1\)[/tex]
- [tex]\(\theta = 45^\circ\)[/tex].
- [tex]\(\tan 45^\circ = 1\)[/tex], so [tex]\(\tan^2 45^\circ = 1\)[/tex].
- [tex]\(\cos 45^\circ = \sin 45^\circ = \frac{\sqrt{2}}{2}\)[/tex], so [tex]\(\cos^2 45^\circ = \frac{1}{2}\)[/tex].
Thus,
[tex]\[ 2 \tan^2 \theta + \cos^2 \theta - 1 = 2 \cdot 1 + \frac{1}{2} - 1 = 2 + \frac{1}{2} - 1 = 1 + \frac{1}{2} = \frac{3}{2}. \][/tex]
#### (b) Find [tex]\(2 \cos^2 \theta - 1\)[/tex]
- [tex]\(\cos 45^\circ = \frac{\sqrt{2}}{2}\)[/tex], so [tex]\(\cos^2 45^\circ = \frac{1}{2}\)[/tex].
Thus,
[tex]\[ 2 \cos^2 \theta - 1 = 2 \cdot \frac{1}{2} - 1 = 1 - 1 = 0. \][/tex]
With these detailed steps, we have solved all the problems.
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.